Pengaruh Manajemen Bakat dan Pengetahuan terhadap Kinerja dan Komitmen Karyawan dalam Perusahaan - Gunawan, Afrio; Rivai, Harif Amali; Lukito, Hendra (Jurnal Informatika Ekonomi Bisnis, 2023)
This study focuses on the key roles played by talent management and knowledge management in improving employee performance, with employee engagement as the mediator variable. Talent management practices, which include career planning, incentives, and organizational support, were found to have a significant influence on employee performance. The main recommendation is to strengthen talent management practices by placing more emphasis on internal talent identification and development, as well as more structured career development programs. Although knowledge management does not have a significant direct influence on employee performance, this study emphasizes the importance of evaluating knowledge management practices. The research uses a quantitative descriptive method. Descriptive methods are used to collect data that can test hypotheses or provide answers to questions related to individual views on certain issues or topics. This method is used to describe and analyze data obtained from respondents in the context of talent management, knowledge management, and its relationship with employee performance and employee engagement. Efforts should be focused on effective knowledge collection, storage and distribution to ensure operational efficiency and continuous employee development. The research then recommends training employees in knowledge management. This will help improve employees' ability to manage and access relevant knowledge, which in turn will improve work efficiency. It is important to note that companies should adopt a proactive approach in regular monitoring and evaluation of factors that affect employee performance. As such, they can identify changes in organizational dynamics and adjust their strategies accordingly. This research provides valuable insights for companies in optimizing employee performance and meeting increasingly complex market demands.